2020
DOI: 10.1177/0896860820953712
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamics in peritoneal dialysis versus intermittent hemodialysis: A transcranial Doppler pilot study

Abstract: This study evaluated intradialytic cerebral hemodynamics measured by transcranial Doppler (TCD) in intermittent hemodialysis (iHD) versus nightly peritoneal dialysis (NIPD). Intradialytic TCD was serially performed in chronic dialysis patients receiving iHD ( n = 10) and NIPD ( n = 10). A linear mixed model was used to model mean flow velocity (MFV), pulsatility index (PI), and mean arterial pressure (MAP) as functions of time and treatment group. Intradialytic cerebral volatility (IDCV) was calculated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These differences in findings may in part result from a higher calcium concentration (1.5 mmol/L) in the dialysis bath, acutely altering vascular tone and arterial stiffness (Mac-Way et al, 2011). In a more recent study, Ghoshal et al (2021) observed a slight increase in cerebral PI during hemodialysis that was not statistically significant. Small sample size, along with limited information regarding study populations and dialysis characteristics, however limit comparison between studies.…”
Section: Pulsatile Components Of Cerebral Blood Velocity Are Reduced ...mentioning
confidence: 97%
See 1 more Smart Citation
“…These differences in findings may in part result from a higher calcium concentration (1.5 mmol/L) in the dialysis bath, acutely altering vascular tone and arterial stiffness (Mac-Way et al, 2011). In a more recent study, Ghoshal et al (2021) observed a slight increase in cerebral PI during hemodialysis that was not statistically significant. Small sample size, along with limited information regarding study populations and dialysis characteristics, however limit comparison between studies.…”
Section: Pulsatile Components Of Cerebral Blood Velocity Are Reduced ...mentioning
confidence: 97%
“…While cerebral blood flow and mean cerebral blood velocity have been measured during hemodialysis, very few studies have evaluated changes in pulsatile components of flow. Recently, Ghoshal et al ( 2021 ) reported an increase in middle cerebral artery blood velocity (MCAv) pulsatility index during hemodialysis, which could contribute to cerebral damage in the long term. However, the study did not provide mechanistic insight into the determinants of increased pulsatility.…”
Section: Introductionmentioning
confidence: 99%